108k views
1 vote
The distance a freely falling body covers in the nth second is given by S(n)=d(n)-d(n-1). Show s(n) in terms of g, in simplified form.

User Martita
by
5.4k points

1 Answer

2 votes

Answer:

Explanation:


s=ut+(1)/(2)gt^2\\if ~the~body~falls~freely,~then~at~t=0,d=0\\s_(n)=d_n=(1)/(2)gn^2\\S_(n-1)=(1)/(2)g(n-1)^2\\distance~covered ~in~nth~second\\S(n)=d(n)-d(n-1)=(1)/(2)gn^2-(1)/(2)g(n-1)^2=\fracg[n^2-(n-1)^2]\\=(1)/(2)g{(n+n-1)(n-n+1)]\\=(1)/(2)g(2n-1)

User Purag
by
4.8k points